Expression of Caspases in the Pig Endometrium Throughout the Estrous Cycle and at the Maternal-Conceptus Interface During Pregnancy and Regulation by Steroid Hormones and Cytokines - Jung, Wonchul; Yoo, Inkyu; Han, Jisoo; Kim, Minjeong; Lee, Soohyung; Cheon, Yugeong; Hong, Minsun; Jeon, Bo-Young; Ka, Hakhyun (Frontiers in Veterinary Science, 2021)
Caspases, a family of cysteine protease enzymes, are a critical component of apoptotic cell death, but they are also involved in cellular differentiation. The expression of caspases during apoptotic processes in reproductive tissues has been shown in some species; however, the expression and regulation of caspases in the endometrium and placental tissues of pigs has not been fully understood. Therefore, we determined the expression of caspases CASP3, CASP6, CASP7, CASP8, CASP9, and CASP10 in the endometrium throughout the estrous cycle and pregnancy. During the estrous cycle, the expression of all caspases and during pregnancy, the expression of CASP3, CASP6, and CASP7 in the endometrium changed in a stage-specific manner, and conceptus and chorioallantoic tissues also expressed caspases during pregnancy. CASP3, cleaved-CASP3, and CASP7 proteins were localized to endometrial cells, with increased levels in luminal and glandular epithelial cells during early pregnancy, whereas apoptotic cells in the endometrium were limited to some scattered stromal cells, not epithelial cells, with increased numbers on Day 15 of pregnancy. In endometrial explant cultures, the expression of most caspases was affected by steroid hormones (estradiol-17β and progesterone), and the cytokines interleukin-1β and interferon-γ induced the expression of CASP3 and CASP7, respectively. These results indicate that caspases are dynamically expressed in the endometrium throughout the estrous cycle and at the maternal-conceptus interface during pregnancy in response to steroid hormones and conceptus signals. Thus, caspase action could be important in regulating endometrial and placental function and epithelial cell function during the implantation period in pigs.